Improving sustainable supply chain performance through organisational culture: A competing values framework approach. Issue 2 (March 2023) - Osei, Martin B.; Papadopoulos, Thanos; Acquaye, Adolf; Stamati, Teta
Abstract: This research adopts the institutional and relational view theories to empirically test the impact of organisational culture (OC) on sustainable supply chain performance (SSCP) and further examines the impact of external integration on their relationship, drawing on a study in the food manufacturing industries in the UK and Greece. Using the mixed method approach, structural equation modelling (SEM) technique was first used to empirically analyse the data from a survey of 315 firms. In addition, insights from 11 interviews from top managers were qualitatively used as the basis to enrich and confirm the findings from the quantitative study. Our findings revealed that in the context of global supply chains only developmental, hierarchical, and group culture components of the competing values framework (CVF) as a model for assessing OC are conducive for achieving a higher SSCP. Although developmental, hierarchical and group cultures are instrumental for SSCP, a strong external integration is still required. Thus, external integration was found to mediate the relationship between the dimensions of OC and SSCP. The results further confirmed a positive relationship between all the dimensions of OC (developmental, group, hierarchical and rational culture) and external integration and a positive impact of external integration on SSCP. This research expands the institutional and relational view theories to examine the effect of OC (using CVF) on SSCP and further reveals the extent of external integration needed in the relationship to enhance SSCP in global supply chains. Supply chain managers are encouraged to adopt integrated competing values, namely, developmental, group, and hierarchical cultures to intensify the external integration in the supply chain to overcome several sustainability challenges and improve SSCP. Highlights: Organisational Culture plays a crucial in the implementation of sustainability practices. Only Developmental, Group and Hierarchical Cultures enables firms to implement and achieve higher sustainability performance. External integration with customers and suppliers is very critical to achieving sustainability performance after instilling sustainability-supportive culture. External integration enables firms to obtain additional information, knowledge, skills and resources needed to enhance sustainability performance.